1957
DOI: 10.1039/jr9570004891
|View full text |Cite
|
Sign up to set email alerts
|

982. Syntheses of substituted amino-, aminovinyl-, and aminobutadienyl-p-quinones

Abstract: Dialkylaminovinylquinones can often be synthesised in good yield from halogenated quinones, acetaldehyde, and secondary amines, isolation of the enamines being unnecessary. A dialkylaminobutadienyl-quinone has been prepared in the naphthalene series, by using 1-diethylaminobutadiene or, less efficiently, a mixture of diethylamine and crotonaldehyde. Replacement of chlorine in the blue dialkylaminovinyltrichlorobenzoquinones can lead to purple or green compounds. For comparison, some reactions between quinones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1962
1962
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The "coupled merocyanine model" is also appropriate for 3 and 4 which exhibit very similar spectral properties in comparison to 1 [21,22]. For 5, however, due to the stronger coupling of the pentamethine moieties via the central CC bond, the localizability indices are significantly lower (cf .…”
Section: A the Electronic States Of 25-diamino -Guinonementioning
confidence: 99%
See 1 more Smart Citation
“…The "coupled merocyanine model" is also appropriate for 3 and 4 which exhibit very similar spectral properties in comparison to 1 [21,22]. For 5, however, due to the stronger coupling of the pentamethine moieties via the central CC bond, the localizability indices are significantly lower (cf .…”
Section: A the Electronic States Of 25-diamino -Guinonementioning
confidence: 99%
“…Whereas in the case of the coupled merocyanine structure 2b the CT contributions play an important role in the description of the lowest excited state of 2, the local excitation of the H-chromophor predominates in respect to the In hexane [21]. 2,5-dichlor-3,6-bis-2-diethylaminovinyl-be~oquinone in dioxan [22]. 1,5-diarnino-naphthochinone(2,6) in dimethyl sulfoxide [23].…”
Section: B the Electronic States Of The Bispyrrol-indigomentioning
confidence: 99%
“…Chloranil undergoes facile nucleophilic displacement reactions with primary and secondary amines, leading to 2,5-bis-amino derivatives (eq 7). 17 Spectroscopic studies have demonstrated that with aliphatic amines at least, the reaction proceeds via a one-electron oxidation of the amine. 18, 19 Chloranil has also been shown to induce the dimerization of diaryldiazomethanes through a reaction believed to involve prior addition across the quinone carbonyl group.…”
Section: -mentioning
confidence: 99%
“…The liberation of ethylene dicllloride on heating is characteristic of colllpounds bearing reactive p-chloroethylmercapto substituents (1). Infrared spectra showed the presence of a phenolic hydroxyl and this was confirllled by acetylation.…”
mentioning
confidence: 96%